Pengembangan Instrumen Pelaksanaan Pencatatan dan Pelaporan Register Kohort Kesehatan Ibu dan Anak (KIA) di Wilayah Kerja Puskesmas Kabupaten Malang - Retno Dewi Prisusanti (Universitas Muhammadiyah Manado, 2023)
Maternal Mortality Rate (MMR) reflects a country's health status, making maternal health a priority in the Millennium Development Goals (MDGs). The Indonesian Demographic and Health Survey (IDHS) reported an increase in MMR from 228 per 100,000 live births in 2007 to 359 per 100,000 in 2012 (Ministry of Health, 2014). A preliminary study in January 2023 identified frequent errors and data loss in the Maternal and Child Health (MCH) cohort register at a community health center (Puskesmas). This study aims to analyze the development of recording and reporting instruments for the MCH cohort register using a descriptive qualitative method. The cohort book serves as a key tool for tracking MCH target achievements, with midwives responsible for recording and reporting PWS KIA data. Their commitment ensures accurate documentation of patient names, parents' names, addresses, and birth details. The assessment of cohort book reporting includes data on pregnant women, childbirth cases, postpartum mothers, high-risk pregnancies, K1, K4, deliveries assisted by healthcare workers, postpartum care visits, and obstetric complications. Additionally, it tracks pregnant, postpartum, and breastfeeding mothers with risk factors detected in the community. Data sources include population projections, maternal cohort registers, and maternal health cards, with primary data gathered from interviews and observations at Singosari and Ardimulyo Community Health Centers. Enhancing recording and reporting mechanisms can improve maternal health monitoring and contribute to reducing MMR.